Quran Teacher: Future Profession or Devotion to the Ummah? - Engkizar, Engkizar; Jaafar, Azhar; Taufan, Muhammad; Rahman, Ikhwan; Oktavia, Gifa; Guspita, Rosi (International Journal of Multidisciplinary Research of Higher Education, 2023)
Quran teachers play a crucial role in preserving and disseminating Islamic religious knowledge. This profession faces a dilemma between devotion to the ummah and the demands of modern professionalism. This study aims to analyze the role, challenges, and prospects of Quran teachers in contemporary social and economic contexts. A qualitative method with a phenomenological approach was chosen for this research. Data were collected from one hundred and five Quran teachers selected through purposive sampling and analyzed thematically using NVivo 12 software. The results indicate that, while the role of a Quran teacher is still regarded as noble and meaningful, practitioners encounter economic difficulties and lack social recognition. Therefore, strategies are needed to enhance the quality and professionalism of Quran teachers and to strengthen their role in society. This research contributes to a deeper understanding of the role of Quran teachers and its implications for the development of Islamic society.